2019
DOI: 10.1128/mbio.02765-18
|View full text |Cite
|
Sign up to set email alerts
|

Mucor circinelloides Thrives inside the Phagosome through an Atf-Mediated Germination Pathway

Abstract: Mucormycosis is an emerging fungal infection that is often lethal due to the ineffectiveness of current therapies. Here, we have studied the first stage of this infection—the germination of Mucor circinelloides spores inside phagocytic cells—from an integrated transcriptomic and functional perspective. A relevant fungal gene network is remodeled in response to phagocytosis, being enriched in crucial functions to survive and germinate inside the phagosome, such as nutritional adaptation and response to oxidativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
102
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(104 citation statements)
references
References 67 publications
2
102
0
Order By: Relevance
“…Our transcriptomic analysis found that all of these marker genes were also controlled by NCRIP during saprophytic growth (S1 Dataset), and thus, they were employed here to validate the transcriptional pre-activation observed in the mutants rdrp1 Δ and r3b2 Δ without macrophages (Fig 3C). We found that the four marker genes showed significant induction in the two mutants without macrophages, similar to the previously reported increased expression observed in the wildtype during phagocytosis [13], indicating that NCRIP controls the response to phagocytosis by repressing it during non-stressful conditions.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Our transcriptomic analysis found that all of these marker genes were also controlled by NCRIP during saprophytic growth (S1 Dataset), and thus, they were employed here to validate the transcriptional pre-activation observed in the mutants rdrp1 Δ and r3b2 Δ without macrophages (Fig 3C). We found that the four marker genes showed significant induction in the two mutants without macrophages, similar to the previously reported increased expression observed in the wildtype during phagocytosis [13], indicating that NCRIP controls the response to phagocytosis by repressing it during non-stressful conditions.…”
Section: Resultssupporting
confidence: 89%
“…Here, we have directly analyzed the transcriptomic profiles in NCRIP key mutants, identifying a substantial number of DEGs in both rdrp1 and r3b2 mutants compared to the wild-type strain. However, a significantly lower number of genes were regulated in these mutants upon phagocytosis compared to the complex response observed in the wild-type strain [13]. The principal component analysis and the comparison of the four profiles among them further confirmed this strong bias among samples.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Mucoralean species are the causative agents of mucormycosis, an emerging fungal infection with extremely poor clinical outcomes, probably as a consequence of their innate resistance to all current antifungal drugs 27,28 and their ability to evade host innate immunity 29,30 . In spite of their clinical relevance, limited information is available on essential biological processes in these fungal pathogens, especially nuclear division and cell cycle.…”
Section: Discussionmentioning
confidence: 99%